PENGARUH SISTEM PENGENDALIAN AKUNTANSI TERHADAP HUBUNGAN DESENTRALISASI PENGAMBILAN KEPUTUSAN DENGAN KINERJA PADA ORGANISASI PEMERINTAHAN DI JAWA TIMUR (Equilibrium: Jurnal Ekonomi-Manajemen-Akuntansi, 2007)
This research wants to find empiric evidences that accountancy controlling system affect the relation between decision making decentralization and the performance of government organization in East Java. Questioners was sent to 85 respondents, that are the chief some official department and the chief of sub department (Education Department, Health Department as well as, Transmigration and Labor Force Department. Each of the answers was analyzed using Doubled Linear Regression. The research's result shows that the level increasing in decision making decentralization in department office cause the increasing in the performance; also that the relation between decision making decentralization and performance can not be influenced by the accountancy controlling system, either in a higher of lower accountancy controlling system.